Enhancing the performance of water-based PVT collectors with nano-PCM and twisted absorber tubes - Anwer B. Al-Aasama; Adnan Ibrahim; Ubaidah Syafiq; Kamaruzzaman Sopian; Bassam M. Abdulsahib; Mojtaba Dayer (International Journal of Renewable Energy Development, 2023)
The study investigated the thermal performance of a photovoltaic thermal (PVT) collector with a twisted absorber tube and nanoparticle-enhanced phase change material (nano-PCM). The PVT collector consisted of twisted absorber tubes, a container filled with nano-PCM, and a photovoltaic (PV) panel. To assess its efficiency, five different configurations were tested using an indoor solar simulator. The configurations analyzed were as follows: (a) an unenhanced PV panel, (b) PVT with circular absorber tubes (C-PVT), (c) PVT with twisted absorber tubes (T-PVT), (d) C-PVT with nano-PCM (C-PVT-PCM), and (e) T-PVT with nano-PCM (T-PVT-PCM). The thermal, photovoltaic, and combined photovoltaic-thermal efficiencies were evaluated at varying mass flow rates (0.008-0.04kg/s) and a constant solar irradiance of 800W/m2. Among the configurations tested, the T-PVT-PCM configuration demonstrated the highest performance. Specifically, at a mass flow rate of 0.04kg/s, solar irradiance of 800W/m2, and an ambient temperature of 27°C, it achieved photovoltaic, thermal, and combined photovoltaic-thermal efficiencies of 9.46%, 79.40%, and 88.86%, respectively. The utilization of twisted absorber tubes in the design notably improved thermal efficiency by enhancing heat transmission between the liquid and the tube surface. Furthermore, the implementation of T-PVT-PCM led to a significant reduction in surface temperature. Compared to the unenhanced PV panel, it lowered the surface temperature by approximately 30°C, and when compared to C-PVT-PCM, it reduced it by around 10°C. Notably, T-PVT-PCM outperformed the unenhanced PV panel by exhibiting a 34.5% higher photovoltaic efficiency. Overall, the study highlights the performance of the PVT collector with twisted absorber tubes and nanoparticle-enhanced phase change material. The innovative design achieved remarkable thermal efficiency, reduced surface temperatures, and significantly enhanced photovoltaic efficiency compared to traditional configurations. These findings contribute to the development of more efficient and versatile solar energy systems with the potential for broader applications in renewable energy technology.